ヒガシ ナンキョク ラングホブデ ニ オケル センルイ ノ ジュン セイサン セイ ノ スイテイ - 伊野, 良夫; イノ, ヨシオ; Ino, Yoshio (1992)
P(論文) 1988年1月にラングホブデの雪鳥沢で採取したコケ塊(Grimmia lawiana, Bryum pseudotriquetrumおよびB. pseudotriquetrumとCeratodon purpureusの混生塊)の光合成, 呼吸速度を現地で2台の赤外線CO_2分析計と温度制御付き同化箱を使用して測定した。同時に光強度と蘚表層の温度を記録した。KAPPEN et al. (Polar Biol., 9,415,1988)の用いた重回帰式に基づいて, 純光合成速度とコケ温度・光強度との関係式をつくった。この重回帰式とOHTANI et al. (JARE Data Rep., 152,216p., 1990)によって測定された雪鳥沢の微気象データを使って, 雪鳥沢に生育するコケ塊の1988年1月から1989年1月までの年間の有機物生産量を計算し, 230g~296gdw・m^<-2>の値を得た。この値はDAVIS (Ecol. Monogr., 51,125,1981)によるシグニー島の群落で報告された純生産量の下限値に近い。 Field measurements of net photosynthesis and dark respiration (CO_2 exchange) of moss colonies were carried out at Langhovde, East Antarctica from 9 to 17 January 1988. Each colony growing at the Yukidori Valley, Langhovde was composed of Grimmia lawiana, Bryum pseudotriquetrum or the mixture of Ceratodon purpureus and B. pseudotriquetrum. Microclimatic data (photosynthetic photon flux density and moss temperature) in the assimilation chamber were recorded at the same time. A simple model to estimate the net photosynthetic rate and dark respiration rate on the basis of the microclimatic data was developed on KAPPEN'S model (KAPPEN et al. : Polar Biol., 9,415 1988). Net primary production of these moss colonies was calculated with the microclimatic data recorded separately at the Yukidori Valley from January 1988 to January 1989 (OHTANI et al. : JARE Data Rep., 152,1990). The estimated net production rates of moss colonies growing in the upper reaches of the Yukidori Valley ranged from 8.8 to 11.3 mol CO_2m^<-2>・y^<-1>, or from 230 to 296 gdw m^<-2>・y^<-1>. departmental bulletin paper